2021
DOI: 10.5650/jos.ess21091
|View full text |Cite
|
Sign up to set email alerts
|

How to Control Powder Alignment to Maximize Functionality and Performance of Color Cosmetics and Sunscreen

Abstract: IntroductionTitanium dioxide and iron oxides are used as functional powders in color cosmetics and sunscreen formulas, along with other compounds such as surfactants, emollients, and preservatives 1 . The development of functional powders that can form a uniform layer on the skin is critical to their functionality in cosmetics and sunscreens to attain two major benefits, i.e. esthetics and protection 2 . Our skin tends to be exposed to harmful environments, including various types of light, such as UV and blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The predispersion (140 ml) thus prepared was mixed with 500 g of Zirconia beads having a diameter of 1 mm in the grinding pot of the bead mill (EASY NANO RMB, AIMEX CO., LTD), and grinding was continued for 45 min at 1405 rpm. The dispersion was then diluted with an identical volume of the liquid to make the final weight ratio of the powder to the liquid at 1.0:7.0 to adjust the viscosity approximately at 5.0 × 10 −2 Pa s. The stability of the dispersions has been verified in our previous study by SEM observation [13]. The rheological texture of each dispersion was thus almost identical to each other.…”
Section: Methodsmentioning
confidence: 83%
See 3 more Smart Citations
“…The predispersion (140 ml) thus prepared was mixed with 500 g of Zirconia beads having a diameter of 1 mm in the grinding pot of the bead mill (EASY NANO RMB, AIMEX CO., LTD), and grinding was continued for 45 min at 1405 rpm. The dispersion was then diluted with an identical volume of the liquid to make the final weight ratio of the powder to the liquid at 1.0:7.0 to adjust the viscosity approximately at 5.0 × 10 −2 Pa s. The stability of the dispersions has been verified in our previous study by SEM observation [13]. The rheological texture of each dispersion was thus almost identical to each other.…”
Section: Methodsmentioning
confidence: 83%
“…In our previous study, the surface pseudo‐HLB of the treated powders was found to be an important index for forming their uniform layer [13]. Seven types of surface‐treated powders, TS , DG , PM , TS / DG , DG / PM , TS / PM and TS / DG / PM samples, having pseudo‐HLB in the range of 3.5–8.5 were prepared in this study (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations